How Smart Is a Smartphone? A Survey Study on The Use of Smartphone Among Students of English Education State University of Makassar - Dio Tri Putra Iskandar; Kisman Salija; Samtidar Samtidar (Universitas Negeri Makassar, 2022)
This study aims to determine how the use of smartphones for learning, especially English by students majoring in English Education at Makassar State University. This study involved 122 students as participants using a purposive random sampling method where the sample had to meet two criteria, namely, having a smartphone and students from the Department of English Education. The questionnaire is a research instrument used in this study. Then the data that has been collected is analyzed deductively and then described descriptively. The results of the study are divided into 4 categories, namely the contribution of smartphones in learning, the use of smartphones for learning purposes, smartphone features, and smartphones for English language skills. In each category, it shows that most of the respondents support the use of smartphones in learning, especially in improving their English skills.